Overcoming mobbing : a recovery guide for workplace aggression and bullying - Duffy, Maureen P.; Sperry, Len (Oxford University Press, 2014)
"Mobbing is a destructive social process in which individuals, groups, or organizations target a person for ridicule, humiliation, and removal from the workplace. It can lead to deteriorating physical and mental health, workplace violence, and even suicide. Studies indicate that as many as 37% of American workers have experienced workplace abuse at some time in their working lives. Overcoming Mobbing is an informative, comprehensive guidebook written for the victims of mobbing and their families who often can't make sense of the experience or mobilize resources for recovery. In an engaging, reader-friendly style, the book distinguishes mobbing from bullying in that it takes place within organizational or institutional settings and involves organizational dynamics. Mobbing is not about the occasional negative experience at work; it is ongoing negative acts, both overt and covert, over time, that erode workers' confidence in themselves and in their workplaces and that no amount of sophistication or maturity can make sense of. Duffy and Sperry, leading authorities on this special type of aggression, provide effective strategies for recovery from mobbing as well as for prevention, and they demystify the experience through the use of case vignettes. More than a simple self-help book, this volume brings the concept and terminology relating to mobbing into the public vocabulary by virtue of its strong foundation in psychological and organizational research. It offers a detailed presentation of the causes and consequences of mobbing, helps readers avoid falling into the trap of misplacing blame, and holds organizations at the center of responsibility for preventing the abuse. In addition to those who have experienced mobbing themselves, this book is an invaluable resource for workplace managers and human resources personnel who wish to prevent or reverse mobbing within their own professional settings"--Provided by publisher